CHIPPING PERFORMANCE OF ADVANCED POTATO HYBRIDS AND NEW VARIETIES BEFORE AND AFTER ON-FARM STORAGE - Marwaha, R. S.; Pandey, S K; Singh, S V; Minhas, J. S. (Potato Journal, 2013)
Seven advanced processing hybrids and six new potato varieties grown under cooler northwestern plains were evaluated for chipping quality and some important processing related chemical constituents before and after 75 days of storage in a farm store (16-38 oC, RH 37-80%). At the time of storage, MP/97-583 and MP/97-921 among hybrids and Kufri Chipsona-2 among cultivars produced very good colour quality chips (colour score up to 3). Hybrid MP/97-921 produced maximum tuber dry matter(25.5%) and chip yield (35.7%), while hybrid MP/97-583 contained lowest amounts of reducing sugars (27mg/100 g fresh wt). There were large variations in the contents of sucrose, free amino acids, total phenolics and enzymic discoloration among the hybrids and varieties. After 75 days of storage, three additional hybrids, viz., MP/97-625, MP/97-644, HT/92-621 and one cv Kufri Chipsona-1 also produced chips of acceptable colour, besides MP/97-583, MP/97-921 and Kufri Chipsona-2. Both, MP/97-583 and MP/97-92, were identified as most suitable for chipping as they produced chips of good colour quality with high yield before and after 75 days of storage in a farm store with tuber weight losses well within 10%.